Disruption in the meat industry new technologies in nonmeat substitutes - Swann, Christopher (Business economics (Cleveland, Ohio), 2023)
© National Association for Business Economics 2023, Springer Nature or its licensor (e.g. a society or other partner) holds exclusive rights to this article under a publishing agreement with the author(s) or other rightsholder(s); author self-archiving of the accepted manuscript version of this article is solely governed by the terms of such publishing agreement and applicable law.